Designing a Social Entrepreneurship Model with a Social Capital Approach in Khorasan Razavi Welfare Organization - Nasrin Hasanpour; faride Hashemiannezhad; Mahmood Ghorbani (Iranian Journal of Educational Research)
Objective: The present study was conducted with the aim of designing a social entrepreneurship model with a social capital approach in the Khorasan Razavi Welfare Organization. Methods: The research method used in terms of data type was a mixed research method. In this study, three sources of data were interviewed, including elites and faculty members, managers and assistants, and employees, to examine different perspectives and obtain more comprehensive and in-depth data regarding the design of a social entrepreneurship model with a social capital approach in the Khorasan Razavi Welfare Organization. Since semi-structured interviews were used in the qualitative phase of this study, the three-stage coding method of Strauss and Corbin (1998) was used to analyze the data obtained from the interviews, namely open, axial, and selective coding. A researcher-made questionnaire was used to collect data in the quantitative phase. Confirmatory factor analysis was used to confirm each of the variables and the items related to each of them. Results: The results showed that causal, contextual, interventional, and strategic factors play an effective role in social entrepreneurship with a social capital approach. Conclusions: The results obtained from this study can be utilized to formulate strategies aimed at enhancing social entrepreneurship through the lens of social capital within welfare organization and other organizations.